Integrating ESG Principles into Sustainable Fisheries Resource Management: A Strategic Framework for Indonesia's 2045 Blue Economy Vision - M. Azizul Khakim; Fathur Rosi (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Marine ecosystems face escalating risks from overfishing, habitat degradation, pollution, and climate change, threatening both biodiversity and the livelihoods of coastal communities dependent on fisheries. Despite growing global commitments to sustainable ocean governance, fisheries management frameworks often lack integrated mechanisms that simultaneously address environmental, social, and governance (ESG) dimensions. This study examines how an ESG framework can be applied to mitigate marine ecosystem risks and advance sustainable fisheries resource management, with particular attention to Indonesia's 2045 Blue Economy Vision. Using a qualitative approach based on literature review and policy analysis, this research identifies key environmental risks (e.g., overexploitation and ecosystem degradation), social dimensions (e.g., community welfare and equitable resource access), and governance gaps (e.g., regulatory enforcement and stakeholder accountability) within the fisheries sector. The findings suggest that integrating ESG principles into fisheries policy can enhance ecosystem resilience, improve regulatory compliance, and strengthen long-term economic sustainability. This study contributes to the discourse on sustainable ocean governance by proposing an ESG-based strategic framework that aligns fisheries management with national blue economy targets, offering practical implications for policymakers, industry stakeholders, and coastal communities seeking to balance ecological preservation with economic growth toward 2045.